The Economic Crisis of 2008-2009: Governance and Consumer Democracy - Dorval Brunell (Norteamérica)
The article begins with an overview of the causes of the economic and financial crisis that struck in the fall of 2008. It then sets out to show how the failure to give due consideration to collective consumer interests and representation led to a lopsided interpretation of the role control agencies were expected to play. It concludes with the idea that effective political involvement by consumers is an essential safeguard in a democracy and an important factor for softening the impact of economic crises on consumers in the future.